Answer:
x = 3
Step-by-step explanation:
Simplifying
4 + -7x = 1 + -6x
Solving
4 + -7x = 1 + -6x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '6x' to each side of the equation.
4 + -7x + 6x = 1 + -6x + 6x
Combine like terms: -7x + 6x = -1x
4 + -1x = 1 + -6x + 6x
Combine like terms: -6x + 6x = 0
4 + -1x = 1 + 0
4 + -1x = 1
Add '-4' to each side of the equation.
4 + -4 + -1x = 1 + -4
Combine like terms: 4 + -4 = 0
0 + -1x = 1 + -4
-1x = 1 + -4
Combine like terms: 1 + -4 = -3
-1x = -3
Divide each side by '-1'.
x = 3
Simplifying
x = 3